Analisis Pengaruh Sikap Konsumen terhadap Iklan Rinso di Televisi Studi pada Perempuan di Kabupaten Lombok Timur - Indranopa, Rian; Agustina, Fitria Ika; Hikmi, Henni Comala; Martasya, Polan Ensi (Valid: Jurnal Ilmiah, 2025)
The type of research to be conducted is descriptive. The purpose of this study is to determine consumer attitudes towards Rinso detergent advertisements on television. Determination of respondents using purposive sampling of 100 respondents. Data collection techniques with interviews, observations and questionnaires and data collection tools using questionnaires. To analyze consumer attitudes towards Rinso advertisements, the Fishbein Attitude Model is used. After analyzing data from the answers of 100 respondents, it can be seen that each respondent has a different attitude between one and another towards Rinso advertisements on television when viewed from their attributes. Based on the 5 categories of attitudes, it shows that respondents who strongly do not accept are 0 percent, respondents who are less accepting are 1 percent, respondents who are neutral are 48 percent, respondents who accept are 51 percent, and respondents who strongly accept are 0 percent. However, when viewed from the results of the Fishbein Analysis as a whole, the average score is 0.36 and when calculated in the attitude score interval class, it is in the class between 0.36 - 0.41. This shows that the category of consumer attitudes towards Rinso advertisements on television in the Study of Women in East Lombok Regency is neutral